2007
DOI: 10.1080/02640410701287172
|View full text |Cite
|
Sign up to set email alerts
|

Physiological characteristics of America's Cup sailors

Abstract: The aim of this study was to assess the physiological profile of America's Cup grinders and mastmen, by measuring energy expenditure during sailing and assessing their aerobic and anaerobic fitness. The study focused on estimating the energy used during grinding activity, by measuring oxygen uptake (VO(2)) during sail setting in real sailing conditions. In the laboratory, using an arm-cranking ergometer, we measured VO(2peak) during an incremental maximal exercise test and total energy expended during the effo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 21 publications
(21 reference statements)
0
33
1
1
Order By: Relevance
“…The mean VO 2 at OBLA of the sailors in the present study was 71% of VO 2max which is less than that typically reported in elite cyclists (~86% (Mujika and Padilla 2001)) and well trained kayakers (81% (van Someren and Oliver 2002)). The nature of grinding during America's Cup yacht racing is highly intermittent and characterised by short bouts of maximal effort interspersed by longer rest intervals (Bernardi et al 2007;Neville 2008). This intermittent activity profile may explain the lower OBLA of grinders compared to the continuous activities of cycling and flat water kayaking.…”
Section: Minmentioning
confidence: 99%
See 4 more Smart Citations
“…The mean VO 2 at OBLA of the sailors in the present study was 71% of VO 2max which is less than that typically reported in elite cyclists (~86% (Mujika and Padilla 2001)) and well trained kayakers (81% (van Someren and Oliver 2002)). The nature of grinding during America's Cup yacht racing is highly intermittent and characterised by short bouts of maximal effort interspersed by longer rest intervals (Bernardi et al 2007;Neville 2008). This intermittent activity profile may explain the lower OBLA of grinders compared to the continuous activities of cycling and flat water kayaking.…”
Section: Minmentioning
confidence: 99%
“…There are typically five or six designated grinders in the crew of 17, however, all athletes assist with grinding, with the exception of the helmsman. It has been suggested that America's Cup grinding utilises both anaerobic and aerobic energy systems, depending on the intensity of racing (Bernardi et al 2007), but the physiological characteristics of America's Cup sailors are poorly understood and very little research has been published on standing arm cranking.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations